2022
DOI: 10.1186/s13148-021-01220-4
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic biomarkers of ageing are predictive of mortality risk in a longitudinal clinical cohort of individuals diagnosed with oropharyngeal cancer

Abstract: Background Epigenetic clocks are biomarkers of ageing derived from DNA methylation levels at a subset of CpG sites. The difference between age predicted by these clocks and chronological age, termed “epigenetic age acceleration”, has been shown to predict age-related disease and mortality. We aimed to assess the prognostic value of epigenetic age acceleration and a DNA methylation-based mortality risk score with all-cause mortality in a prospective clinical cohort of individuals with head and n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Finally, we here calculated the epigenetic age of patients and controls by the analysis of HFD methylomes. Epigenetic age is a recently established biomarker of aging 48 . DNA methylation-based aging clocks is a composite measure of DNA methylation (DNAm) levels across specific CpG sites along the genome and may be calculated from methylome raw data using different computational tools 38 , 49 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we here calculated the epigenetic age of patients and controls by the analysis of HFD methylomes. Epigenetic age is a recently established biomarker of aging 48 . DNA methylation-based aging clocks is a composite measure of DNA methylation (DNAm) levels across specific CpG sites along the genome and may be calculated from methylome raw data using different computational tools 38 , 49 51 .…”
Section: Discussionmentioning
confidence: 99%
“…65,72,[82][83][84] EAA is not only associated with risk of cancer but also the prognosis of cancer. [85][86][87][88][89][90] Independent of chronological age and traditional CVD risk factors, greater EAA was a promising predictor for incident fatal coronary heart disease, peripheral arterial disease, heart failure, and ischemic stroke outcome. 74,[91][92][93] Moreover, EAA was associated with higher risk for incident CVD events, and a predictor for dementia, 94 Alzheimer's Disease, 95 Parkinson's Disease, 96 and posttraumatic stress disorder (PTSD).…”
Section: Epigeneticsmentioning
confidence: 99%
“…Longitudinal studies have further revealed an association between EAA and a higher risk of all‐cause mortality, 80,81 and specific leading causes of deaths, such as cancer‐related mortality and CVD‐related mortality in EAA 65,72,82–84 . EAA is not only associated with risk of cancer but also the prognosis of cancer 85–90 . Independent of chronological age and traditional CVD risk factors, greater EAA was a promising predictor for incident fatal coronary heart disease, peripheral arterial disease, heart failure, and ischemic stroke outcome 74,91–93 .…”
Section: Molecular and Cellular Ageing Biomarkersmentioning
confidence: 99%
“…Further research is needed to understand how epigenetic age and DNA methylation clocks may help us anticipate, prevent, and overcome diseases related to ageing. Clearly, epigenetic clocks have a big potential as clinical biomarkers ( 115 , 116 ).…”
Section: Metabolism and Epigenetics Deregulation In Diseasementioning
confidence: 99%